Pengaruh Pemberian Probiotik Limosilactobacillus reuteri dalam Tatalaksana Kolik Infantil - Ahmad Iqbal Romdloni (Jurnal Kedokteran Syiah Kuala, 2023)
Infantile colic is a condition involving full-force prolonged crying in healthy and thriving infants with no apparent cause. In addition to causing long term effects on infants, this condition also affects parents, including: anxiety, stress, maternal depression risk, and shaken baby syndrome. On the other hand, probiotic administration is proven to reduce crying duration and frequency by balancing gastrointestinal microbiote and metabolite secretion that eases the symptoms of colic. This study was conducted to determine the effect of probiotic administration, particularly Limosilactobacillus reuteri, in infantile colic management. The method used in this research is literature study. Population in this study includes study articles about probiotics and infantile colic with samples taken from 12 articles in SCIMAGO indexed international journals published from 2016 to 2021. This research took place from May to November 2021. Results of 12 research articles shown that the administration of probiotic L. reuteri is able to reduce the incidence of infantile colic characterized by crying frequency and duration decrease and other symptoms, such as : bloating, abdominal muscle tension, flushing, and postural changes, significantly on breastfed infants. Probiotic administration on babies colic is safe. L. reuteri probiotic shows good and consistent effectiveness compared to other probiotics.